Subjective Activity of Preschoolers as the Main Objective of the “Child-Teacher-Parents” Triad - Borisovna Bystrai, Elena; Alexandrovich Artemenko, Boris; Dmitrievna Kirienko, Svetlana; Nikolaevna Evtushenko, Irina; Sergeevna Mikerina, Alena (Opción, 2019)
Abstract. The article presents the results of diagnosing the formation of preschool- ers’ subjective activity, teachers’ professional activities affecting its level and the participation of parents in joint activities aimed at the development of children’s subjective activity. The development of the latter is one of the components of the child’s social formation, i.e. a complex phenomenon during which children acquire norms of human society and assert themselves as social subjects. The authors of the article have developed and tested an array of methods entitled “Psychological and pedagogical monitoring of educational activities aimed to develop the sub- jective activity of preschoolers”. If directors and teachers of preschool education institutions introduce the above-mentioned methods, they will be able to obtain the data necessary for planning and implementing the educational process aimed at the development of children’s subjective activity in preschool education institutions. The study is based on three methodological approaches: axiological, activity-based and qualimetric.